The Sacred Matrix: Reclaiming the Feminine Body as Ontological Vocation in Hebrew and Malagasy Cosmologies - Rafaramalala Dyna; Robijaona Rahelivololoniaina Baholy (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
This theological reflection embarks on a profound comparative exegesis, plumbing the depths of the female body's symbolic resonance within two disparate yet remarkably convergent sacred traditions: ancient Hebrew biblical anthropology and the Malagasy cosmovision. Employing a rigorous interdisciplinary methodology that weaves together exegesis, symbolic anthropology, linguistics, and contextual theology, this study illuminates how both traditions imbue the feminine form with rich layers of sacred, ontological, and relational meaning. Central to this exploration is the Hebrew term neqēvāh (נְקֵבָה), commonly rendered "woman." Far from a mere biological descriptor, neqēvāh is here unpacked as a potent theological metaphor — a signifier of ontological openness, spiritual receptivity, and sacred fecundity. This understanding is then brought into a generative dialogue with evocative Malagasy expressions such as mitondra rano ("water bearer"), trano zaza ("child’s house"), and tratra masoandro ("touched by the sun"). Strikingly, these seemingly disparate metaphors converge towards a unified theological apprehension of femininity not as a state of biological passivity, but as a dynamic, vivifying space of creation, transmission, and cosmic mediation. This inter-epistemic approach not only unveils the profound richness inherent in localized sacred traditions but also underscores the urgent theological imperative to revalorize the female figure within contemporary theological discourses. It invites us to perceive the feminine body as a locus of divine immanence and a conduit for cosmic flourishing.